1997
DOI: 10.1210/jcem.82.4.3860
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Diet Restrictions Modify the Circadian Time Structure in Humans. A Study on Plasma Gastrin, Insulin, Glucose, and Calcium and on Gastric pH1

Abstract: The rule of Ramadan (1 month of food and water intakes restricted to night hours) is followed by the majority of the Moslem fraction of the human population, but the possible consequences of this long-lasting modification of food intake schedule on public health have not yet been extensively documented. Therefore, a group of healthy control subjects and a group of healed duodenal ulcer patients were studied before (controls), during (both groups), and after (both groups) the month of Ramadan. The time-restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Higher IOP values may be a result of a decline in the activity of the drug by 4 pm, when the effect of fasting becomes apparent. Secondly, habit modifications during Ramadan have been shown to affect the sleep cycle and circadian rhythms in several studies (16)(17)(18)(19). Bogdan et al (16) observed that during Ramadan the serum cortisol level increased in the afternoon; the ordinary morning rise was delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Higher IOP values may be a result of a decline in the activity of the drug by 4 pm, when the effect of fasting becomes apparent. Secondly, habit modifications during Ramadan have been shown to affect the sleep cycle and circadian rhythms in several studies (16)(17)(18)(19). Bogdan et al (16) observed that during Ramadan the serum cortisol level increased in the afternoon; the ordinary morning rise was delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Then, unlimited food intake and hydration are allowed till dawn. The obligation to eat only within a short overnight span leads to several behavioral changes in sleep (19,20), alertness (21), meal times (21,22) and eating schedule (21,22). Additionally, in adults, physiological changes may be observed during Ramadan observance such as dehydration (14,19,(23)(24)(25)(26)(27)(28)(29), metabolic responses (24,25,27,28) and the circadian variation of body temperature, cortisol and melatonin (30,31).…”
Section: Contextmentioning
confidence: 99%
“…Several studies examined the health effects of making intermittent changes in mealtimes to accommodate the fasting requirements during Ramadan through sleep/wakefulness episodes. Findings from these studies showed that altered mealtimes, sleep patterns, and circadian rhythms were associated with increased risk factors for metabolic, endocrine, and gastrointestinal problems [27][28][29]. Clinical evidence demonstrated that an interrupted or restricted sleep pattern during the normal circadian nighttime cycle in Ramadan causes daytime fatigue, which has been associated with impaired cognitive and kinetic physical functioning [30].…”
Section: Introductionmentioning
confidence: 99%